Structural and chemical analysis of 3D printed metal products - et al., Maxim Kuznetsov (International Journal of Advanced Science and Technology, 2019)
Making complex metal work with additive techniques is becoming more and more important for modern industry. Such metal work can be produced by arc surfacing. Highly productive surfacing with concentrated power source allows layer-by-layer formation of solid structures, thus, realizing the principle of additive manufacturing. In additive manufacturing the metal work is produced by melting some powder or wire. The methods which use powder as a consumable material are low productive, their application for manufacturing large-size constructions is limited and the powder is used inefficiently. Surfacing with consumable electrode in the shielding gas atmosphere can be applied as the basic electric arc method of layer-by-layer formation of solid structures. Application of this process ensures good atomic interaction of the layers. Thus, the aim of this paper is to study the microstructure, the mechanical behavior and the chemical composition of the layers produced by electric arc layer-by-layer surfacing with consumable electrode in the shielding gas atmosphere. The optical metallography method was applied to study the structure and the chemical composition was estimated by atomic emission spectral analysis. The microhardness was measured by diamond points indention. The research showed that the walls of the products manufactured by electric arc layer-by-layer surfacing have the gradient structure. It is only the last surfaced layer that has the dendrite structure. The underlayers are exposed to secondary heat treatment due to the heat emission from the upper layer. The percentage ratio change of manganese, silicon and carbon in the surfaced layers was observed. The percentage ratio of chrome and nickel through the layers was determined by the chemical composition of the surfaced material. There is an opportunity of producing a flawless wall of the hull structure.